Pemanfaatan Situs Kampung Tenun Samarinda Sebagai Sumber Pembelajaran Sejarah Pada Kurikulum Merdeka di Kalimantan Timur - Norhidayat, Norhidayat (Lambung Mangkurat University, 2023)
Samarinda Weaving Village is a village that has been around for a long time in Samarinda City, East Kalimantan. This village is located in Samarinda Seberang which is densely populated and the majority are woven cloth craftsmen. In this research, it starts from how the use of weaving villages as a source of history learning in Samarinda City and what things can be used related to this learning resource in schools. Apart from that, this research will also discuss how to utilize Weaving Village as a Source of Learning History in accordance with the independent curriculum policy. The method used in this study is a qualitative method with data collection in the form of interviews with data collection techniques, data presentation, data reduction and verification as well as conclusions. In this research, we will find out how the role of the teacher will play in utilizing historical learning resources in Samarinda City. In addition, how is the application of the independent learning curriculum in preparing students who are active and creative and able to hone students' thinking skills. Thus, the purpose of the independent curriculum and how it is implemented in learning history and the use of weaving villages will be answered in this study. In addition, we can also see the activeness of students in learning history by utilizing learning resources in accordance with the independent curriculum.